YouTube Channel: An Alternative Social Media to Enhance EFL Students’ Speaking Skill - Muhammad Ilyas; Miranti Eka Putri (J-SHMIC : Journal of English for Academic, 2020)
The aim of this study is to know wether there is or not significant effect of using YouTube channel to students’ speaking skill. The use of YouTube channel can make easier for students to receive lessons, motivate students in learning, so what is the purpose of education can be achieved well. YouTube encourages positive learning attitude if it is incorporated in classroom teaching to supplement language learning especially speaking. The design of this study is experimental research that was conducted at English language study program of Universitas Islam Riau. The sample consist of 48 students from the first semester. After applying YouTube channel in learning, the results of the study showed a significant improvement. Based on the data of SPSS, the value of sig. (2-tailed) was 0,000 which is not greater than the probability value of 0.05. (0.000 < 0.05). It can be concluded that Ho is rejected and H1 is accepted, means that there is significant effect of using YouTube channel towards students’ speaking skill.